Interaction between culture and economy in traditional handicraft villages in Vietnam = Interakcje między kulturą a gospodarką w tradycyjnych wioskach rzemieślniczych w Wietnamie - Dinh Thi Van Chi (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research in traditional handicraft villages shows that economy and culture mutually interact in both positive and negative ways since culture is a human resource which not only brings economic benefits, but also strongly impacts the formation of economic mindset, stimulates creativity and enhances people's responsibility to the community. Additionally, Vietnamese small-scale peasant culture is a condition for arising bad practices of small business, reducing economic development. Economy acts as a material resource for cultural development, contributing to creating a healthy society. However, economy also pushes human into material race, creating psychology of external preferences, while disregarding cultural and traditional values and reducing community cohesion.
Keywords: interakcje między kulturą a gospodarką; wzajemne interakcje pomiędzy kulturą a gospodarką; kultura i gospodarka wsi trudniących się rękodziełem; interactions between culture and economy; mutual interactions between culture and economy; culture and economy of handicraft villages